Ruthenium-106 plaque brachytherapy for uveal melanoma. Issue 12 (15th May 2015) - Tarmann, Lisa; Wackernagel, Werner; Avian, Alexander; Mayer, Christoph; Schneider, Mona; Winkler, Peter; Langmann, Gerald
Abstract : Background: To report on local tumour control, eye preservation and visual outcome after ruthenium-106 brachytherapy for uveal melanoma. Methods: Medical records of 143 eyes with uveal melanoma, treated by ruthenium-106 brachytherapy between 1997 and 2012 at one single centre, were included. Primary outcome measures were local tumour control, eye preservation and visual outcome. The influence of patient, tumour and treatment parameters on outcome was analysed by time to event analysis and competing risk regression. Results: The median overall follow-up was 37.9 months. Tumour control: recurrent tumour growth was observed in 17 patients. The estimated local tumour recurrence rate at 12, 24 and 48 months after irradiation was 3%, 8.4% and 14.7%, respectively. The only significant risk factors for tumour recurrence were age (p=0.046) and reduced initial visual acuity (VA, p=0.045). No significant difference could be shown for tumour size or tumour category (T1–T2 vs T3–T4), and for any other tumour or treatment parameters (including combined transpupillary thermo-therapy (TTT)). Eye preservation: The likelihood of keeping the eye 12, 24 and 48 months after irradiation was 97.7%, 94.7% and 91.8%, respectively. Most significant risk factors for secondary enucleation were initial VA (p<0.001), tumour height (p=0.002) and tumour category (p=0.015). Vision: The chances of keeping VA of 20/200 or better at 1, 2 and 5 years after treatment were 86.4%, 80.8% and 61.7%, respectively. Patients receiving sandwich-TTT showed significantly worse visual outcomes. Conclusions: Ruthenium-106 brachytherapy appears to be a useful treatment regarding tumour control, eye preservation and visual function. Adjunct sandwich therapy resulted in worse visual outcome.